Death due to Congenital Transmesenteric Hernia in an Adult: A Rare Autopsy Case Report - Chaudhary, Gopal; Shrestha, Sabnam; Shakya, Arbin (Journal of Institute of Medicine Nepal, 2024)
Death due to congenital transmesenteric hernias are uncommon in adults. We report a rare autopsy case, of an unmarried 25 years old female who presented with congenital transmesenteric hernia with no previous history of surgery or trauma. Autopsy examination revealed 180 cm of strangulated small intestine herniated through a defect in the small bowel mesentery. This case highlights the importance of considering rare conditions like congenital transmesenteric hernia in the differential diagnosis of acute abdomen and the awareness of high level of suspension with prompt advanced imaging and surgical intervention.